CULTURAL THEORY AND MANAGERIAL VALUES: EXAMINING TRUST AS A MOTIVATION FOR COLLABORATION. (27th August 2015) - CONNER, THADDIEUS W.; NOWLIN, MATTHEW C.; RABOVSKY, THOMAS; RIPBERGER, JOSEPH T.
Abstract : Public administration theorists have long argued that values of administrative actors fundamentally shape the quality and nature of the public services they provide. While there has been some work in recent years to measure values in the public sector like Public Service Motivation, we know relatively little about the role that other (more basic) values play in shaping managerial behaviour. To fill this gap,  we argue that Cultural Theory (CT), a prominent theory within research on risk and public opinion,  provides a general framework for operationalizing and measuring the values of public managers, which (if pursued) allows scholars to directly test important yet untested hypotheses about the relationship between values and managerial decision‐making. To explore this proposition, we use data from a recent survey of American Indian education directors in public school districts to examine the relationship between cultural worldviews and managerial motivation to engage actors in collaborative arrangements.